‘To honour the treaty, we must first settle colonisation’ (Moana Jackson 2015): the long road from colonial devastation to balance, peace and harmony - Mutu, Margaret (Journal of the Royal Society of New Zealand, 2019)
Māori leaders in New Zealand continue the battle to end British colonisation. The aim is to restore the balance between Māori and the Crown guaranteed in the treaty that Māori and the British Crown agreed to in 1840 so that we can live in peace and harmony. Early European visitors subjected our ancestors to numerous atrocities. Relying on the Doctrine of Discovery, they illegitimately usurped our power and dispossessed us, leaving us in a state of poverty, deprivation and marginalisation. They fabricated myths to justify their criminal activities, set up an illegitimate parliament with unfettered powers, passed laws legalising their crimes and then covered it up with amnesia. They established the Waitangi Tribunal in 1975 to inquire into breaches of the treaty, not realising that it would dismantle the myths and look beneath the amnesia. Governments then instigated the ‘treaty claims settlement’ process to extinguish all Māori claims, remove Māori rights and entrench colonisation. Research undertaken has shown that Māori loathe this process and do not accept that settlements are full and final. Research on constitutional transformation has identified a possible solution. The first step towards that goal involves implementing the United Nations Declaration on the Rights of Indigenous Peoples.
Keywords: UNDRIP; colonisation; colonisation myths; constitutional transformation; crown; kāwanatanga; māori rights; oral history; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty breaches; treaty settlements; waitangi tribunal

Māori Issues 2017-2018 - Mutu, Margaret (2019)

The treaty claims settlement process in New Zealand and its impact on Māori - Mutu, Margaret (2019)
This article considers research conducted on the impact of the Crown’s treaty claims settlement policy on Māori in New Zealand. It provides a brief background to the Treaty of Waitangi and the subsequent British colonisation process that relied on the Doctrine of Discovery in breach of the treaty. It outlines how colonisation dispossessed Māori of 95 percent of their lands and resources, usurped Māori power and authority and left them in a state of poverty, deprivation and marginalisation while procuring considerable wealth, prosperity and privilege for British settlers. The work of the Waitangi Tribunal, the commission of inquiry set up to investigate those breaches, is considered, as is the Crown’s reaction to the 1987 Lands case in developing its treaty claims settlement policy. The Crown unilaterally imposed the policy despite vehement opposition from Māori. Since 1992, it has legislated more than seventy ‘settlements’. The research shows that overall, the process has traumatised claimants, divided their communities, and returned on average less than one percent of their stolen lands. Proposals for constitutional transformation have drawn widespread support from Māori as a solution to British colonisation. United Nations treaty-monitoring bodies have recommended that the government discuss this with Māori
Keywords: colonisation; constitutional transformation; crown policy; law; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal